SISTEM PENYELENGGARAAN PENDIDIKAN NON FORMAL DI INDONESIA - Ruhyanani, Hindama (PEDAGOGY, 2017)
Non-formal system of Islamic education in Indonesia act to support national education program. However, this education takes place outside the schooling system is established, conducted independently or an important part of broader activities, which deliberately made to serve specific learners in achieving learning goals. Non-formal education is one kind of education in Indonesia. Other types of education is formal education and informal education. Non-formal education can be held by individuals or foundations that have the ability to manage independently